The Dynamics of International Migration and Settlement in Europe A State of the Art - Kraal, Karen; Penninx, Rinus; Berger, Maria (Amsterdam University Press, 2006)
A fundamental issue in society today, migration has been undergoing a new dynamic transformation, calling for new policy approaches. This new dynamic is not yet understood clearly, let alone that adequate policy answers for 'the managing' of these new migration processes and the consequences for receiving and sending societies are within. This comprehensive overview of migration research conducted throughout the IMISCoe network of European research analyses the influx of various types of immigrants in Western Europe post World War II, mostly to large cities, as well as the reactions of the native populations and governments to the changes and pressures brought about by immigration.